Anaerobic co-digestion of swine manure and chicken feathers: Effects of manure maturation and microbial pretreatment of feathers on methane production. (June 2020) - Schommer, Vera Analise; Wenzel, Bruno München; Daroit, Daniel Joner
Abstract: Manures and feathers are abundant wastes from the meat supply chain. Although manures are used in anaerobic digestions to produce methane, feathers recalcitrance might be challenging. Methane production was assessed during mesophilic anaerobic co-digestion (Co-AD) of swine manures with untreated/pretreated feathers. Diluted fresh (DF; 1:2) or matured (DM; 1:1) manures were used both as Co-AD inoculums and main substrates. Co-substrates were feathers (FF) and feather hydrolysates produced through microbial degradation (FH); in Controls, total solids (TS) were adjusted with sterilized manure. In DF experiments, 5.6% TS (27.7% from co-substrate) and 6.8% TS (40.4% from co-substrate) yielded similar methane production [0.48 L CH4/g volatile solids (VSinitial )]. With FF, methane production showed a two-step decomposition pattern. At 6.8% TS, FH reduced yields (43%), possibly through ammonia inhibition. In DM experiments, at 4.60% TS (12.1% from co-substrate) and 5.15% TS (21.3% from co-substrate), methane production was superior with FH (0.16–0.19 L CH4/g VSinitial ); FF decreased yields (15–25%), suggesting delayed biodegradation. Modified Gompertz model fitted best to kinetic data. FF and Controls displayed similar methane yields, and FH affected production in a concentration-dependent manner. Microbial pretreatment could increase methane production by improving feathers biodegradability. FH represents a nitrogen-rich substrate for Co-AD with nitrogen-deficient biomasses. Graphical abstract: Image 1 Highlights: Methane production from co-digestion of swine manures and recalcitrant feathers. Matured manure as inoculum and main substrate negatively affected methane yields. Untreated feathers displayed no adverse effects on final methane production. Microbial pretreatment to obtain feather hydrolysates for increased methane yields. Pretreated feathers presented concentration-dependent effects on methane production.